Does the urban wage premium differ by pre-employment status?. Issue 10 (3rd October 2019) - Hamann, Silke; Niebuhr, Annekatrin; Peters, Jan Cornelius
ABSTRACT: This paper investigates whether the density of local labour markets in Germany impacts on the wage of new employment relationships and whether corresponding urbanization economies differ significantly across distinct types of transitions to employment. The results suggest rather small static urbanization benefits. Doubling employment density increases the wage of new employment relationships by 1.0–2.6%. Moreover, benefits seem to accrue only to persons experiencing job-to-job transitions and the short-term unemployed, but not to the long-term unemployed. It is supposed these differences point to matching advantages in large urban labour markets from which only some job seekers benefit.